Foetal echoencephalography and Doppler ultrasonography of the middle cerebral artery in canine foetuses - Feliciano, M. A R [UNESP]; Nepomuceno, A. C. [UNESP]; Crivalero, R. M. [UNESP]; Oliveira, M. E F [UNESP]; Coutinho, L. N. [UNESP]; Vicente, W. R R [UNESP] (Wiley, 2013)
Objectives: This study aimed to evaluate the characteristics of the brain and vascular indicesof the middle cerebral artery of canine foetuses. Methods: Twenty-five bitches were selected. Tissue development, echogenicity, echotexture and brain echobiometric data were studied, and the major structures were identified between the 5th and 8th gestational weeks. The area and volume of the brain mass (BMA and BMV), cranial area and volume (AC and VC), brain mass index (BMI) and brain volume index (BVI) were determined. A single ultrasound examination was performed during each studied week (6th, 7th and 8th). Doppler ultrasonography was performed to assess the maximum and minimum velocity, resistance and pulsatility index of middle cerebral artery of the foetuses. Results: Echoencephalography was performed to evaluate the morphological characteristics of the central nervous system. Cerebral echobiometry indicated an increase in area and volume of the hemispheres and cranium (P<0·001) but no changes in BMI or BVI over the gestational period studied. Doppler ultrasonography identified increases in peak systolic velocity (P=0·0188) and end diastolic velocity (P=0·0274) and decreases in resistance index (P=0·0002) and pulsatility index (P<0·001). Clinical Significance: Echoencephalography and spectral Doppler ultrasonography of the middle cerebral artery in canine foetuses might be a useful technique for prenatal care. © 2013 British Small Animal Veterinary Association.
Keywords: animal; animal disease; blood flow; blood flow velocity; brain circulation; dog; Doppler flowmetry; echography; female; fetus; fetus echography; gestational age; hemodynamics; middle cerebral artery; physiology; pregnancy; prenatal development; vascularization; Animals; Blood Flow Velocity; Cerebrovascular Circulation; Dogs; Female; Fetus; Gestational Age; Hemodynamics; Middle Cerebral Artery; Pregnancy; Regional Blood Flow; Ultrasonography, Doppler; Ultrasonography, Prenatal